Tongkonan is One of The Cultural Symbols For The Toraja People That Has Noble Values - Asniati Kuasa Rombelinggi'; Bahar Bahar; Akbar Abu Thalib; Heppy Lismayanti (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Tongkonan is a traditional house of Torajan people. Tongkonan is a place to discuss or conduct traditional affairs, not just an extendeed family home and a place to maintain community ties. The aim of this research is to identify the meanings contained in tongkonan. In this research, researcher using qualitative methods, with the aim of researchers to find out the meaning of tongkonan for Torajan people. The meanings of tongkonan from Torajan cultural perspective are; tongkonan is symbol of lineage and family identity, tongkonan served as the center of traditional government, tongkonan is a center of traditional ceremonies and rituals, and tongkonan as symbol of cosmic harmony (Aluk Todolo). The research result show that Tongkonan is a source of pride and splendor for the entire Torajan tribe, as this traditional house serves not only as a residence but also as a kinship symbol for the entire Torajan family, even if some family members have passed away. Tongkonan is not only a place to live with extended family, but also a place to perform various traditional rituals and ceremonies, also tongkonan is not something that is 'chosen', but something that is determined by descent.